Rancang Bangun Alat pendeteksi Tingkat Tekanan Bunyi Terhadap Respon Membran Timpani Berbasis Serat Optik - Harmadi Harmadi; Dolly Irfandy; Miftah Ikhwani (Jurnal Fisika Unand, 2021)
It has been designed a sound pressure level detection for response of tympanic membrane based on optical fiber with extrinsic method. The fiber optic sensor is used to measure the sound pressure level by utilizing the output voltage change. The sound level pressure values obtained are displayed on OLED display. Testing tools with sound level meter comparison tool to test sound pressure level in poly ENT patients. The test results show that at sound pressure level measurement with frequency 200 Hz to 300 Hz, the average accuracy is 93.42% for right ear, at the same time for left ear the average accuracy is 94.58%. The test of compliance measurement the average accuracy is 77.97% for the right ear, at the same time for the left ear the average accuracy is 70.74%. The testing of the appliance to patient in Andalas University hospital poly ENT were detect the values of sound pressure level 60 dB to 65 dB.Â